Rodent Models of Streptozotocin-Induced Diabetes as Suitable Paradigms for Studying Diabetic Kidney Disease - Liu, Haoxin; Wang, Yucheng; Wang, Ying; Yan, Liang-Jun (Free Radicals and Antioxidants)
The purpose of this correspondence is to highlight the usefulness of Streptozotocin (STZ)-induced type 1 diabetes for studying Diabetic Kidney Disease (DKD) which is also known as diabetic nephropathy.1 DKD is a major microvascular complication of diabetes regardless of type 1 or type 2 diabetes.1 DKD is also a leading cause for the development of end stage renal failure.1 The main features of DKD is thickening of the glomerular basement membrane caused by accumulation of matric glycoproteins and collagens, resulting in increased albumin secretion and a decreased glomerular filtration rate.2,3 Abnormal structural changes such as mesangial expansion, podocyte cell death, and tubular interstitial fibrosis also contribute to glomerular hyperfiltration and proteinurea in DKD,2,3 leading to decline in kidney function. Despite advanced knowledge garnered over the years on DKD pathogenesis and anti-DKD strategies, no effective treatments for DKD are presently available. Therefore, this unmet medical need will continue to drive intensive and vigorous researches to understand the underlying pathological mechanisms of DKD, in hopes to discover potential targets for DKD therapeutic purpose.